The Role Of Parental Communication In Monitoring Smartphone Users At Age Teenagers In Penggalan Village, Tebing Syahbandar District - Kamalia, Handayani; Idris, Muhammad; Maryadi (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
The role of communication between parents and adolescents can be seen as the efforts made by parents in monitoring and directing the development of adolescents. By creating communication that can affect the relationship between the two, both physically and psychologically. One technology, namely a smartphone, is a sophisticated tool that can penetrate information anywhere and anytime, to find out information from any angle without considering the influence that will be received by its users. Therefore, this research aims to find out how effective and efficient the role of parental communication is in monitoring smartphone users in their teens. In this study, the type of research that the authors use is qualitative research. While the approach used is descriptive analysis, which is a research method that looks at objects or conditions, systematically, factually and accurately describes the facts that have been investigated and the results can be used for the future. The dominant factor that causes the role of communication between parents and adolescents is not good, resulting in many teenagers losing direction and their growth and development being hampered due to the influence of communication technology in the form of smartphones that are continuously used without any restrictions and good directions